2018
DOI: 10.1088/1361-6528/aab3f5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of electronic and magnetic properties in InSe nanoribbons: edge effect

Abstract: Quite recently, the two-dimensional (2D) InSe nanosheet has become a hot material with great promise for advanced functional nano-devices. In this work, for the first time, we perform first-principles calculations on the structural, electronic, magnetic and transport properties of 1D InSe nanoribbons with/without hydrogen or halogen saturation. We find that armchair ribbons, with various edges and distortions, are all nonmagnetic semiconductors, with a direct bandgap of 1.3 (1.4) eV for bare (H-saturated) ribb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The conduction band minimum (CBM) and valence band maximum (VBM) are highlighted in red with states being distributed both above and below the Fermi level. The result is in accordance with the previous theoretical results . Meanwhile, the density of states (DOS) of InSe in conjunction with projected DOS of Se and In were also studied, as shown in Figure S1, Supporting Information.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The conduction band minimum (CBM) and valence band maximum (VBM) are highlighted in red with states being distributed both above and below the Fermi level. The result is in accordance with the previous theoretical results . Meanwhile, the density of states (DOS) of InSe in conjunction with projected DOS of Se and In were also studied, as shown in Figure S1, Supporting Information.…”
Section: Resultssupporting
confidence: 89%
“…In Figure , we scheme the top and side views of InSe nanoribbons of A11H in Figure a and Z6H in Figure c. Similarly to define the width of graphene nanoribbon (GNR), there are mainly two kinds of edge styles: armchair InSe nanoribbon (aISN) and zigzag InSe nanoribbon (zISN), and the widths can be set as the number of dimer/zigzag lines along the transport direction . We found that armchair ribbons are nonmagnetic and direct band‐gap semiconductors, while all zigzag ribbons are metallic, and show intrinsic ferromagnetism on the edge atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to H-AISNs, where vertical mirror plane (σ v ) is present, opposite edges of H-ZISNs are terminated by different (In and Se) atoms, which results in the structure with lower symmetry. Compared to H-ZISNs, all armchair InSe nanoribbons are predicted to be nonmagnetic semiconductors with a direct band gap of ∼1 eV at the Γ point [20]. Here, we mainly focus on magnetic properties and, therefore, consider only H-ZISNs.…”
Section: First-principles Calculationsmentioning
confidence: 99%
“…Very recently, density functional theory (DFT) studies point to the possibility of edge magnetic ordering in InSe nanoribbon [20]. Similar to graphene, edge spin-polarization is predicted for all zigzag nanoribbons with/without hydrogen or halogen saturation.…”
Section: Introductionmentioning
confidence: 97%